Activation of the NLRP3 inflammasome by human adenovirus type 7 L4 100-kilodalton protein - Duan, Yali; Zhu, Yun; Zhang, Linlin; Wang, Wei; Zhang, Meng; Tian, Jiao; Li, Qi; Ai, Junhong; Wang, Ran; Xie, Zhengde (Frontiers in Immunology, 2024)
Human adenovirus type 7 (HAdV-7) is a significant viral pathogen that causes respiratory infections in children. Currently, there are no specific antiviral drugs or vaccines for children targeting HAdV-7, and the mechanisms of its pathogenesis remain unclear. The NLRP3 inflammasome-driven inflammatory cascade plays a crucial role in the host's antiviral immunity.Our previous study demonstrated that HAdV-7 infection activates the NLRP3 inflammasome.Building upon this finding, our current study has identified the L4 100 kDa protein encoded by HAdV-7 as the primary viral component responsible for NLRP3 inflammasome activation. By utilizing techniques such as co-immunoprecipitation, we have confirmed that the 100 kDa protein interacts with the NLRP3 protein and facilitates the assembly of the NLRP3 inflammasome by binding specifically to the NACHT and LRR domains of NLRP3. These insights offer a deeper understanding of HAdV-7 pathogenesis and contribute to the development of novel antiviral therapies.